Regional impacts of climate change and its relevance to human evolution. (28th October 2020) - Sánchez Goñi, María Fernanda
Abstract: Abstract: The traditional concept of long and gradual, glacial–interglacial climate changes during the Quaternary has been challenged since the 1980s. High temporal resolution analysis of marine, terrestrial and ice geological archives has identified rapid, millennial- to centennial-scale, and large-amplitude climatic cycles throughout the last few million years. These changes were global but have had contrasting regional impacts on the terrestrial and marine ecosystems, with in some cases strong changes in the high latitudes of both hemispheres but muted changes elsewhere. Such a regionalization has produced environmental barriers and corridors that have probably triggered niche contractions/expansions of hominin populations living in Eurasia and Africa. This article reviews the long- and short-timescale ecosystem changes that have punctuated the last few million years, paying particular attention to the environments of the last 650, 000 years, which have witnessed key events in the evolution of our lineage in Africa and Eurasia. This review highlights, for the first time, a contemporaneity between the split between Denisovan and Neanderthals, at ~650–400 ka, and the strong Eurasian ice-sheet expansion down to the Black Sea. This ice expansion could form an ice barrier between Europe and Asia that may have triggered the genetic drift between these two populations.